2024
DOI: 10.1007/s10764-023-00414-2
|View full text |Cite
|
Sign up to set email alerts
|

Play Behavior Varies with Age, Sex, and Socioecological Context in Wild, Immature Orangutans (Pongo spp.)

Julia A. Kunz,
Sonja S. Falkner,
Fikty Aprilinayati
et al.

Abstract: Play is thought to serve different purposes at different times during ontogeny. The nature and frequency of play are expected to change accordingly over the developmental trajectory and with socio-ecological context. Orangutans offer the opportunity to disentangle the ontogenetic trajectories of solitary and social play with their extended immature phase, and socio-ecological variation among populations and species. We evaluated the frequency of play in 39 immature individuals across two populations (Pongo pyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…We found that there was no significant difference between mothers and fathers with regard to the time they spent playing with their infants. In the species where parents do get involved in playful interactions, especially at a young age, these playful interactions are often exhibited with the primary caregiver i.e., mothers in chimpanzees Pan troglodytes (Pellegrini & Smith, 2005) or orangutans Pongo spp (Kunz et al, 2024). In species where males take an active role in immatures caretaking, they also show an important involvement in playful interactions, sometimes more than the mothers: In horses, stallions are the preferred play partners compared to the mothers and they also actively seek playful contact with their foals in contrast to the mothers (Šandlová et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that there was no significant difference between mothers and fathers with regard to the time they spent playing with their infants. In the species where parents do get involved in playful interactions, especially at a young age, these playful interactions are often exhibited with the primary caregiver i.e., mothers in chimpanzees Pan troglodytes (Pellegrini & Smith, 2005) or orangutans Pongo spp (Kunz et al, 2024). In species where males take an active role in immatures caretaking, they also show an important involvement in playful interactions, sometimes more than the mothers: In horses, stallions are the preferred play partners compared to the mothers and they also actively seek playful contact with their foals in contrast to the mothers (Šandlová et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A factor that could explain those differences between species is the presence or absence of other immatures. It has been suggested that immatures prefer playing with their peers, and will play with adults if there are no other options (Kunz et al, 2024;Pellis & Iwaniuk, 2000;Poirier, 1970). Ultimately it has been suggested that, by playing with infants, adults facilitate the immatures' acquisition of species-specific signals and skills employed in various social interactions (Enomoto, 1990;Mackey et al, 2014;Paquette & StGeorge, 2023;Sutton-Smith, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations